An Analysis of Lexicons in The Malik Sumpah Ceremony in Sembiran Village, Buleleng Regency - Oktapiani, Ni Komang Ayu Tria (STKIP Agama Hindu Singaraja, 2023)
This research was designed in the form of a descriptive qualitative study. This research aimed to find out the lexicons that the priests use in the Malik Sumpah ceremony in Sembiran village and to describe the cultural meaning of the lexicons used by the priests in the Malik Sumpah ceremony. This research was conducted in Sembiran village, Tejakula district, Buleleng regency. The research data were obtained through observation by attending the ceremony in Sembiran village, interviewing the three informants, and documenting the lexicons in that ceremony. The researcher selected the informants based on a set of criteria. Four instruments were used in this research, namely an observation sheet, interview guide, interview sheet, and recorder. The results showed that the Malik Sumpah ceremony in Sembiran village had forty-one lexicons, including eight lexicons found in the series of events, nineteen lexicons found in Malik Sumpah facilities, and six lexicons found in kind of sacrifices. Eight lexicons were found in kind of offerings.